TP8.1.4 Can volume replacement with local perforator flaps reduce the trauma to patients caused by mastectomies and cost of reconstructions in breast cancer treatment?. (28th October 2021) - Karagiannidis, Georgios; Mortimer, Caroline; Tuffaha, Hussein; Peerlinck, Inga; Mallidis, Evangelos
Abstract: Aims: Improved screening and raised breast awareness raises the demand for breast cancer treatment. 25% - 45% of breast cancer treatment will be mastectomies, some of them followed by reconstruction. Mastectomy +/-reconstruction is a traumatic procedure which affects quality of life of patients plus extra cost for NHS for reconstruction. Can the "relative new" technique of local perforator flaps, reduce the volume of mastectomies (and subsequently reconstructions) in a District General Hospital? Methods: Retrospective review of yearly breast cancer treatment operations from 2017 to 2020 in Ipswich Hospital. Results: 1094 surgical operations performed for breast cancer. In 2017, 85/292 (29, 1%) had mastectomy and 13/292 (4, 4%) had local perforator flap surgery. In 2018, the number of mastectomies was 74/299 (24.7%), while 4/299 (1.3%) patients underwent local perforator flap surgery. In 2019, the amount of perforator flaps increased to 24/305(7.8%) while the mastectomies remained in equivalent percentages [72/305 (23.6%)]. Finally, in 2020, despite the presence of COVID19 and the decrease in surgical management of cancer, 16/198(8.5%) had local perforator flaps surgery and only 34/198 (18%) had mastectomy.0/57 (0, 00%) of the local perforator flaps failed. Conclusions: Local perforator flaps have resulted in 11.1% reduction in mastectomy rate (also reducing reconstructions). The exchange of mastectomy and reconstruction with breast conserving surgery and local perforator flap reduces the operating time and cost of cancer treatment without compromising oncological outcome or patient satisfaction.